The secret circle-the initiation and the captive part 1 - Smith, L. J. (Lisa J.) (HarperTeen, 2008)
Contains the first two novels in The Secret Circle series in which Cassie moves from California to New England to live with her mom and grandmother where she discovers she is one in a long line of witches, is initiated into a coven at her school, and upsets the balance of power when she falls in love with Adam, another witch's boyfriend.